Spiritual Guidance With Dhikr Therapy for People with Mental Disorders (Analysis of the Implementation of Spiritual Guidance With Dhikr Therapy at the Jalma Sehat Kudus Foundation) - Bastomi, Hasan (LP2M IAIN kUDUS, 2022)
This study aims to reveal the implementation of spiritual guidance with dhikr therapy for people with mental disorders at the Jalma Sehat Kudus Foundation. The research on the implementation of spiritual guidance with dhikr therapy in people with mental disorders was carried out using a qualitative approach with the type of field research with data collection techniques using Interview, Observation and Documentation. The results showed that first, the method of Islamic spiritual guidance with dhikr therapy in dealing with people with mental disorders at the Jalma Sehat Kudus Foundation is the group therapy method and the direct therapy method. Second, there are two stages in the implementation of Islamic spiritual guidance with dhikr therapy in dealing with mental disorders patients at the Jalma Sehat Kudus Foundation, namely: (1) The preparation stage, is the stage where the supervisor assisted by nurses identifies problems, designs action plans, and solves problems. patient problems. (2) The implementation stage, namely by reading dhikr sentences such as tasbih, istigfhar, and sholawat sentences. Third, the material in Islamic spiritual guidance with dhikr therapy is an explanation of the nature of God, human duties, commendable and despicable morals, and gratitude. The implication of this research is to provide knowledge about the implementation of dhikr therapy, because dhikr based on various studies can help overcome mental disorders.